Volatilitas Harga Emas sebagai Safe Haven dan Hedge di Indonesia: Model GARCH - Meyga Refina Putri Andini; Marthunis Efendi (Jurnal Ekonomi dan Bisnis, 2026)
This study examines the risk characteristics and price volatility of gold in Indonesia over the 2015–2024 period. The analysis applies the GARCH (1,1) model to assess the magnitude of price fluctuations and the market’s ability to respond to changing economic conditions. Based on 2,563 daily observations, the annual volatility of the domestic gold market is estimated at around 21.11%. This figure reflects active but still reasonable price movements. Another important finding is the market’s fast recovery, where about half of the impact from economic shocks typically fades within approximately 1.5 days. This indicates that risk in the gold market tends to be short-lived. The study also highlights the shifting role of gold under different market conditions. During periods of severe stress, such as the 2020 pandemic, both gold prices and volatility increased sharply, confirming its function as a short-term safe haven. In more stable periods, volatility declines quickly and prices follow a gradual upward trend, reinforcing gold’s role as a long-term hedging instrument. Overall, these findings suggest that gold is not only a safe asset but also a resilient and adaptive market for investors in Indonesia.